Micro-Level Sustainability Transition Pathways of Institutional Food Services in France - Martin, Guillaume; Pujos, Lise; Magrini, Marie-Benoit (Frontiers in Sustainable Food Systems, 2022)
Very few studies have dealt with sustainability transitions in the agrifood sector, especially in institutional food services (IFS), and notably at a micro level. Based on 29 interviews with head cooks in France, we characterized the micro-level sustainability transition pathways that institutional catering units have been following, taking essentially four sustainable practices into consideration: organic food use, ultra-processed food use, vegetarian meals and waste management. We identified four transition pathways according to the speed, size, dimensionality and time-period of changes in those practices. We showed how these pathways are linked to the diversity of transition contexts; internal (e.g., skills) and external (e.g., local suppliers) resources and constraints. This original empirical study revealed the diversity and feasibility of sustainability transition pathways in IFS. It also showed that they do not require unreasonable increases in resources. Positive narratives on transitions need developing, together with diagnosis tools to guide them.